A modelling of the role of social networks in market mechanism: Social ties as screening tools in price discrimination - Károly Miklós Kiss; Kinga Edőcs (Hungarian Academy of Sciences, Institute of Economics, 2018)
One of the most relevant and exciting issues in the latest decades in economics had been the asymmetric information and uncertainty, and their effects on market processes and efficiency. Some studies show that markets where information problems or/and uncertainty arise tend to be "networked", and some studies propose that use of social networks can mitigate adverse selection and moral hazard problems, but this area is still under-developed. Price discrimination is a representative situation where asymmetric information vigorously appears. The firms rarely have precise information about the types of individual customers (their important features, preferences or willingness-to-pay), but can use incentive tools and screening mechanisms. Use of signaling and screening can reduce the cost of incentive under asymmetric information. We develop a model to show that social embeddedness of buyers and some relevant features of their social network can be used for screening to mitigate the information problem in pricing decisions.
Keywords: D8; L11; Z13; 330; asymmetric information; nonlinear pricing; incentive contracts; social network; social embeddedness